Bahasa pasar Malaysian Chinese / Ooi Sing Ee - Ooi Sing, Ee (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2024)
What is Bahasa Pasar for Malaysian Chinese? It’s a non-standard Chinese language, and its pronunciation, glossary, and grammar are influenced by dialects such as Cantonese, Hokkien, and Teochew. It is commonly used in markets and unofficial forums. Three scholars published a dictionary in 2022 that collected all the commonly used Basha Huayu of Malaysian Chinese.